Selective bromination of sp3 C-H bonds by organophotoredox catalysis - Kee, Choon Wee (2014)
We report that bromination of aliphatic and benzylic sp3 C[BOND]H bonds can be achieved with visible light photoredox catalysis by using a low loading of Eosin Y disodium salt, an inexpensive organic dye, as a photoredox catalyst. The light source is a low-power household lamp and the reaction can be performed without the need of an inert atmosphere and anhydrous solvent. Easy-to-handle CBr4 is the source of bromine and morpholine is necessary for the reaction. Preliminary experimental and computational studies on the mechanism strongly suggest that an N-morpholino radical is responsible for the C[BOND]H activation step. This led us to propose that this is a radical relay reaction, in which a longer-lived morpholine radical is generated from a CBr3 radical, which is relatively more transient, by a thermodynamically favorable reaction. Additional evidence for the existence of such an N-radical was obtained from radical trapping experiments. The strong preference of this reaction for electron-rich hydrogen atoms, and the high sensitivity to the steric environment around the C[BOND]H bond enables bromination to occur on the relatively stronger C[BOND]H bond (as quantified by bond dissociation enthalpy) on the same molecule. The potential for utilizing this reaction to achieve mild and regioselective bromination of sp3 C[BOND]H bonds in complex molecules is exemplified by the bromination of (+)-sclareolide and acetate-protected estrone.